Gradient-Based Iterative Parameter Estimation Algorithms for Dynamical Systems from Observation Data - Feng Ding; Jian Pan; Ahmed Alsaedi; Tasawar Hayat (Mathematics, 2019)
It is well-known that mathematical models are the basis for system analysis and controller design. This paper considers the parameter identification problems of stochastic systems by the controlled autoregressive model. A gradient-based iterative algorithm is derived from observation data by using the gradient search. By using the multi-innovation identification theory, we propose a multi-innovation gradient-based iterative algorithm to improve the performance of the algorithm. Finally, a numerical simulation example is given to demonstrate the effectiveness of the proposed algorithms.